Heart rate variability in beta-thalassemia patients - Wasarut Rutjanaprom (2018)
Background: Cardiac failure remains the major cause of death in beta-thalassemia major (TM). Reduced heart rate variability (HRV) is associated with a higher risk of arrhythmias after myocardial infarction and heart failure. We evaluated HRV in TM patients and its relationship with hemodynamics and echocardiographic parameters during a 6-month follow-up. Methods: Thirty-four TM patients (19 ± 10 yr) and 20 healthy subjects (17 ± 6 yr) were evaluated. Hematologic, biochemical, echocardiographic and HRV parameters were determined at entry and at 6-month follow-up. Time and frequency domain HRV parameters were analyzed from 24-h recorded electrocardiograms. All TM patients received blood transfusion and chelation therapy. Results: Both time and frequency domain HRV parameters were markedly reduced in TM patients, compared to the control. The significantly improved HRV was seen in correlation with higher hemoglobin (Hb) level when compared within TM group at different time point. No correlation was seen between HRV and serum ferritin, reactive oxygen species (ROS) and non-transferrin bound iron (NTBI). Conclusion: HRV is depressed in TM patients. HRV was significantly correlated with Hb level, suggesting that anemia greatly influences the cardiac autonomic balance. © 2009 John Wiley & Sons A/S.